Recent advances in the understanding and management of ARDS - Peck, Tyler J (F1000Res, 2019)
The acute respiratory distress syndrome (ARDS) remains a common and highly morbid condition despite advances in the understanding and management of this complex critical illness. Recent work has illuminated the heterogeneity within ARDS and demonstrated the likely impact of heterogeneity on the identification of effective therapeutic interventions. Despite these challenges, new data have also informed the standard of care for ARDS and have resulted in the re-evaluation of previously established therapies, including ventilation strategies, pharmacologic interventions, and rescue therapies. As the field of ARDS continues to evolve, innovative approaches will be needed to further define phenotypes within ARDS and design targeted clinical trials.